PENGARUH KOMBINASI PUPUK ORGANIK DAN TARAF UREA TERHADAP KUALITAS VISUAL DAN PRODUKSI RUMPUT RAJA (Pennisetum purpoides) EFFECT OF ORGANIC FERTILIZER IN COMBINATION WITH UREA LEVEL ON VISUAL QUALITY AND PRODUCTION OF KING-GRASS (Pennisetum purpoides) - Hendarto, Eko (Pembangunan Pedesaan, 2005)
A study on King grass (Pennisetum purpoides) cultivation was carried out. The aim was to find an efficient cultivation pattern through the fertilizer application for the efforts to develop a high quality feed crops for supporting the program of whole year forage availability. Factorial experiment method using Completed Randomized Design was applied. Materials used were three kinds of organic fertilizers, i.e., cow dungs, chick and goat manures and urea fertilizer levels (0, 75, 150, 225 kilograms per hectare per defoliation) repeated three times. Variables observed were the height of grass, diameters of false stem, numbers of tree, fresh and dry production. The result of data analysis showed that up to the level of 225 kilograms of urea per hectare per defoliation on the organic fertilizer was unable to reach optimal level of Pennisetum purpoides in order to perform a good visual and production. The organic fertilizer of chicken combined with the level of 225 kilograms of urea per hectare per defoliation enable Pennisetum purpoides to perform a high visual and fresh and dry forages production.